2007
DOI: 10.1097/01.ta.0000232011.59630.93
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Oral Fluconazole in Critically Ill Abdominal Trauma Patients With and Without Abdominal Wall Closure: a Randomized Crossover Clinical Trial

Abstract: The bioavailability of enterally dosed fluconazole was highly variable in both the open and closed abdomen patients. Intravenous administration of pharmaceuticals may provide more reliable serum levels in the first 2 weeks after trauma-related laparotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The lowest and highest C max differed by 14‐fold for oseltamivir and 18‐fold for oseltamivir carboxylate. Although a substantial portion of the intersubject variability in oseltamivir carboxylate concentrations may be due to differences in the number of previous oseltamivir doses, this study also agrees with previous findings that pharmacokinetic variability can be increased in critical illness and multiorgan failure, particularly when an oral drug is administered …”
Section: Discussionsupporting
confidence: 91%
“…The lowest and highest C max differed by 14‐fold for oseltamivir and 18‐fold for oseltamivir carboxylate. Although a substantial portion of the intersubject variability in oseltamivir carboxylate concentrations may be due to differences in the number of previous oseltamivir doses, this study also agrees with previous findings that pharmacokinetic variability can be increased in critical illness and multiorgan failure, particularly when an oral drug is administered …”
Section: Discussionsupporting
confidence: 91%
“…56 However, among critically ill surgical patients, bioavailability may vary greatly and initial therapy via the IV route seems prudent for this population. 57 The recommended dosage for invasive candidiasis in critically ill adults is a loading dose of 800 mg (12 mg/kg) then 400 mg (6 mg/kg) daily. 58 Dosage adjustment is required for patients with renal dysfunction.…”
Section: Fluconazolementioning
confidence: 99%
“…31 The bioavailability of fluconazole in the critically ill has been evaluated and results are mixed. Barquist et al 32 reported a decrease in AUC with enteral administration in critically ill patients after laparostomy. 32 While fluconazole is typically well absorbed in healthy patients, several studies have reported variable enteral bioavailability in critically ill patients with estimates ranging from 77% to 124%.…”
Section: Antifungalsmentioning
confidence: 99%
“…Barquist et al 32 reported a decrease in AUC with enteral administration in critically ill patients after laparostomy. 32 While fluconazole is typically well absorbed in healthy patients, several studies have reported variable enteral bioavailability in critically ill patients with estimates ranging from 77% to 124%. 30 , 33 - 36 These studies also evaluated the effect of enteral nutrition on fluconazole concentrations; two studies found that tube feeds decreased fluconazole absorption and two studies found no effect from tube feeds.…”
Section: Antimicrobialsmentioning
confidence: 99%